Live birth rate following frozen-thawed blastocyst transfer is higher in high-grade day 6 blastocysts than in low-grade day 5 blastocysts - Shi, Wenhao; Zhou, Hanying; Chen, Lijuan; Xue, Xia; Shi, Juanzi (Frontiers in Endocrinology, 2023)
Background: Day 5 (D5) blastocyst is generally given priority to transfer than Day 6 (D6) blastocyst, however, which one should be prioritized to transfer when only low-grade D5 and high-grade D6 blastocysts are available? Methods: A large retrospective cohort study was carried out to evaluate the live birth rate (LBR) following D5 and D6 blastocyst in single frozen-thawed blastocyst transfer (FBT) during Jan 2014 and Dec 2018. A multivariate logistic regression was conducted to evaluate the combined impact of expanded day (D5&6) and blastocyst quality (high-grade/low-grade) on LBR accounting for the potential confounding factors. The biopsied blastocysts form consecutive PGT-A case series during Feb 2013 to Dec 2021 were performed as a supplementary analysis. Results: The LBR achieved in high-grade D6 blastocyst transfer was significantly higher than low-grade D5 blastocyst (50.43% vs 40.70%, aOR 1.54, 95%CI 1.05-2.26, p=0.027). There were no significant differences in preterm birth rate, very preterm birth rate, mean live birth weight, birth weight <1500g and >4000g between two cohorts. As for aneuploidy analysis in PGT, there were 54.55% of euploid blastocysts (30/55) among high-grade D6 blastocysts, significantly higher than 41.39% of euploid blastocysts (565/1365) among low-grade D5 blastocyst (p<0.001). Conclusions: Our data suggested Day 6 blastocyst with high morphology grading should be preferred than Day 5 blastocyst with low morphology grading when selecting blastocyst transfer to short the time of conceiving.